Dataset of PAHs determined in home-made honey samples collected in Central Italy by means of DLLME-GC-MS and cluster analysis for studying the source apportionment - Sergio Passarella; Ettore Guerriero; Luisangela Quici; Giuseppe Ianiri; Marina Cerasa; Ivan Notardonato; Carmela Protano; Matteo Vitali; Mario Vincenzo Russo; Antonio De Cristofaro; Pasquale Avino (Data in Brief, 2022)
This paper would like to show all the data related to an intensive field campaign focused on the characterization of the Polyaromatic Hydrocarbons (PAHs) composition profile in almost 60 honey samples collected in Central Italy. The analytical data here reported are the base for a study aimed to identify the pollution sources in a region. 22 PAHs were analyzed by means of ultrasound-vortex-assisted dispersive liquid-liquid micro-extraction (DLLME) procedure followed by a triple quadrupole gas chromatograph/mass spectrometer (GC-MS). A chemometrics approach has been carried out for evaluating all the data: in particular, principal component analysis and cluster analysis has been used both for the identification of the main natural/anthropogenic pollutants affecting a site and for evaluating the air quality.